2019
DOI: 10.1007/s11010-019-03576-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel tetrahydroacridine derivatives with iodobenzoic moieties induce G0/G1 cell cycle arrest and apoptosis in A549 non-small lung cancer and HT-29 colorectal cancer cells

Abstract: A series of nine tetrahydroacridine derivatives with iodobenzoic moiety were synthesized and evaluated for their cytotoxic activity against cancer cell lines-A549 (human lung adenocarcinoma), HT-29 (human colorectal adenocarcinoma) and somatic cell line-EA.hy926 (human umbilical vein cell line). All compounds displayed high cytotoxicity activity against A549 (IC 50 59.12-14.87 µM) and HT-29 (IC 50 17.32-5.90 µM) cell lines, higher than control agents-etoposide and 5-fluorouracil. Structure-activity relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…The viability and cell cycle analysis results were presented as mean ± standard deviation. All assays were performed in triplicate, and the results were obtained in three independent experiments [35].…”
Section: Biological Assaysmentioning
confidence: 99%
“…The viability and cell cycle analysis results were presented as mean ± standard deviation. All assays were performed in triplicate, and the results were obtained in three independent experiments [35].…”
Section: Biological Assaysmentioning
confidence: 99%
“…The standard analytical wavelength for this complex is 570 nm in a mixture of dimethylsulfoxide (DMSO) (Serva) and Sorensen’s glycine buffer. The experiments were done in triplicate [ 42 ]. The concentration of analyzed compounds was used to determine IC 50 values.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the cell cycle is a tightly regulated process, which is frequently aberrant in lung cancer (Shcherba et al, 2014). By inhibiting the unrestricted cell division and growth of lung cancer cells, cell cycle-related genes have emerged as new targets for the treatment of lung cancer (Girek et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that IGF2BP1 has been traditionally regarded as an oncogene and potential therapeutic target for cancers (Huang et al, 2018). It plays essential roles in embryogenesis and carcinogenesis, regulating the expression of some essential mRNA targets required for the control of tumor cell proliferation, growth, and invasion, and associating with a poor overall survival and metastasis in various types of human cancers (Gong et al, 2016). However, there is no public report on miR1293 and LINC01740 according to a PubMed search.…”
Section: Discussionmentioning
confidence: 99%